PENGUASAAN NEGARA ATAS USAHA-USAHA PERTAMBANGAN MINERAL DI INDONESIA - Ahmad, Ahmad; Mina, Risno; Hipan, Nasrun; Fality, Firmansyah (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2023)
This study aims to determine the state's control authority over mineral mining businesses in Indonesia and what rights and obligations are granted by the state to holders of mining business permits in managing mineral mining. This study uses normative legal research methods. The results of the research and discussion formulate that the state's control authority over mining businesses is of course to support the creation of community welfare. This can be realized if the policies and management of mineral mining by the state through the government can be proven by the actions and decisions of the state or government that can be felt directly by the community. Meanwhile, the rights and obligations granted by the state to holders of mining business permits in managing mineral mining are in the context of supporting sustainable national development and ensuring the effectiveness of the implementation and control of mining business activities in an efficient, effective and competitive manner. In addition to guaranteeing the benefits of mining that are sustainable and environmentally sound, increase people's income, and create jobs, and guarantee legal certainty